Schüler*innen - Studierende - Inklusion Orientierungen auf dem Weg zu differenzsensibler Lehrer*innenbildung? - Oldenburg, Maren (Interdisziplinäre Beiträge zur Inklusionsforschung, 2021)
The implementation of inclusive schools requires a corresponding professionalization of teachers. In addition to inclusion-related knowledge, the students' school and education-related orientations constitute important factors for the teacher acting (Helsper 2018). This dissertation is a qualitative-reconstructive study in the context of research on inclusive teacher education. The study analyses the students' orientations regarding inclusion, exclusion and difference from a praxeological perspective on professionalism (Bohnsack 2020). The study is situated at the interface of educational science and special education. Students of special education, secondary schools and vocational schools were consulted. These students participated in a university seminar about disability, which was affiliated to the project "Qualitätsoffensive Lehrerbildung". During the course of the seminar, the students dealt with the pupils' statements concerning collaborative learning and feelings of belonging and exclusion. As its starting point the study focuses on the observation that pupils' perspectives are only marginally represented in discussions about inclusion. The study addresses the question, if and to what extent the students refer to the pupils' statements in their discussions about inclusion, exclusion and difference. Using the documentary method, four group discussions are analysed and interpreted at two points in time concentrating on implicit knowledge. The results are theoretically classified using a praxeological perspective on professionalism as well as an interactive and situational understanding of difference. Therefore, the findings provide information on which difference-related norms become effective and guide action, and whether the students define themselves from these norms (Bonnet/Hericks 2019). It becomes obvious that the students' orientations are largely characterized by a homogeneity illusion of school and teaching. With the claim of realising inclusive education, tensions such as the reproduction and deconstruction of differences come to light in particular ways that are seemingly difficult for the students to endure. The study aims to focus attention on both the students' and the pupils' perspectives in order to generate insights into the relationship of these perspectives. The central result is that the students hardly recognise the pupils' voices as independent positions in the discussions about inclusion. Instead, they use them as a starting point for shaping their own prospective position as a teacher.